Habitat Selection of Northern Bobwhite in the Rio Grande Plains of Texas - William P. Kuvlesky Jr.; Wendell G. Swank; Nova J. Silvy (National Quail Symposium Proceedings, 2017)
From June 1987 through September 1988, we determined habitat selection by northern bobwhites (Colinus virginianus) in the Rio Grande Plains of south Texas. Habitat components were evaluated at a large scale (100-m circular plots) and fine scale (8-m circular plots) levels of resolution at radiomarked bobwhite locations and at random sites. Data was collected during summer 1987, fall-winter 1987–88, and spring-early summer 1988. On both scales of resolution, during each season, bobwhites were found in more patchier areas than were available. Distance to roads was the only important large scale habitat variable identified. Forbs appeared to be the most important fine scale habitat variable. Grass, shrubs, and bare ground were also identified as important habitat variables. Important fine-scale and large-scale habitat variables were not correlated with one another. Therefore, it is important to examine habitat variables at different scales when studying habitat use by northern bobwhites.
Keywords: northern bobwhite; Colinus virginianus; habitat; habitat interspersion; scale; Texas